The role of atropine in myopia control: insights into choroidal and scleral mechanisms - Huang, Longxiang; Zhang, Jingjin; Luo, Youfang (Frontiers in Pharmacology, 2025)
In this study, we investigate the inhibitory effects of atropine on the progression of experimental myopia by targeting the functions of the choroid and sclera and exploring its potential therapeutic mechanisms. Form deprivation myopia (FDM) was induced in C57BL/6 mice, with treatment groups receiving atropine. We assessed the effects on ocular morphology, extracellular matrix (ECM) protein expression, choroidal and scleral thickness, and choroidal vascular index (CVI) through histopathology, immunofluorescence, and quantitative quantitative polymerase chain reaction (qPCR). In vitro, mouse scleral fibroblasts (MSFs) were treated with Na2S2O4 to induce hypoxia, followed by atropine treatment. Atropine treatment significantly reduced axial elongation and ECM remodeling in FDM mice, as indicated by a decrease in collagen volume fraction. It restored choroidal and scleral thickness and increased CVI, suggesting improved microcirculation. Atropine also modulated ECM protein expression and reduced the hypoxia marker Hypoxia-Inducible Factor-1α (HIF-1α). In vitro, atropine protected MSFs from hypoxia-induced damage, preserved cytoskeletal integrity, and modulated key signaling pathways, including P53 and β-catenin. These findings suggest that atropine holds promise for controlling myopia progression by improving choroidal microcirculation, reducing scleral hypoxia, and regulating ECM remodeling, supporting its therapeutic application in myopia management.